Sunni-Shiah rivalry: myths and reality - Akhmetova, Elmira (KIRKHS IIUM, 2016)
Analyses of the roots of sectarian conflict in the Middle East tend to look at the historical schism between Sunnis and Shias as the fundamental driving factor behind contemporary tensions existing in the entire Muslim world. Discussions on the existence of a “1,400 Year War” between Sunni and Shiah Muslims are today increasingly common. No doubt, differences between Sunnis and Shias, which started at the early years of Islamic caliphate after the death of the Prophet Muhammad (PBUH), regarding his legitimate successor, are real and cannot be denied. Despite some disagreements between Sunni and Shiah interpretations of the Shari’ah, yet, scholars from both sides have long engaged in dialogue and influenced the religious thought of one another for centuries.